SUSTAINABLE FINANCIAL INCLUSION THROUGH FINTECH ADOPTION: INTEGRATING FINANCIAL AND TECHNOLOGICAL PERSPECTIVES: FINANCIAL INCLUSION THROUGH FINTECH ADOPTION: INTEGRATING FINANCIAL AND TECHNOLOGICAL PERSPECTIVES - Emilda; Susi Handayani; Dr. Endah Dewi Purnamasari, SE, MM (Jurnal Ecoment Global, 2026)
Objective: The objective of this study is to investigate the adoption of fintech, specifically Peer-to-Peer (P2P) lending, from both technological and financial perspectives. The aim is to analyze the factors influencing behavioral intention and use behavior, considering the role of financial literacy in the decision-making process Design/Methods/Approach: The theoretical framework underpinning this research is the Unified Theory of Acceptance and Use of Technology (UTAUT), which is extended by integrating financial variables such as price value and risk. These concepts provide a solid foundation for understanding the behavioral factors influencing the adoption of fintech services, specifically in the context of P2P lending. This research employs a quantitative methodology, using Structural Equation Modeling (SEM) to analyze data collected from 250 active P2P lending investors in Indonesia. Data was gathered through a structured questionnaire, with participants selected via purposive sampling to ensure they were familiar with fintech platforms. Findings: The findings revealed that performance expectancy and effort expectancy significantly influence behavioral intention to adopt P2P lending. Additionally, price value and risk have a notable impact on the use behavior of investors. The discussion contextualizes these findings within the theoretical framework, emphasizing the need for transparent cost structures and effective risk management to foster sustainable fintech adoption Originality/Value: This research is original in its integration of financial variables with UTAUT to examine P2P lending adoption. It offers valuable insights into the role of financial literacy in shaping user behavior, contributing to both academic literature and practical applications in fintech development. Practical/Policy implication: This study provides both practical and theoretical implications. Theoretically, it contributes to the understanding of fintech adoption by integrating financial perspectives into the UTAUT framework. Practically, it offers insights into how fintech service providers can enhance transparency and investor education to promote wider adoption and usage.